RETRIEVAL OF LAND SURFACE TEMPERATURE FROM EARTH OBSERVATION SATELLITES FOR GAS FLARING SITES IN THE NIGER DELTA, NIGERIA - O. Morakinyo, Barnabas (FUDMA Journal of Sciences, 2026)
Land Surface Temperature (LST) at gas flaring sites plays an essential role in various aspects such as monitoring vegetation and its growth; agricultural activities and productivity of several plant species; climate change and disaster monitoring. In the Niger Delta, limited researches have been undertaken on the LST measurement at flaring sites using Earth Observation Satellites (EOS) data. This research investigates the recording of LST by EOS for four gas flaring sites in Rivers State, Nigeria. Eleven Landsat 5 Thematic Mapper (TM) and Twenty Six Landsat 7 Enhanced Thematic Mapper Plus (ETM) from October 10, 1984 to March 08, 2013 with  5% cloud contamination were considered. Dark Object Subtraction (DOS) method and Atmospheric Correction Parameter (ATMCORR) Calculator were used to obtain the atmospheric correction (AC) effects parameters for the multispectral and the thermal bands respectively. The emissivity for each site is estimated by using standard values for determined land surface cover from the Look Up Table (LUT). The correction obtained from DOS method was applied to the computed reflectance to get the atmospherically corrected reflectance that was used for the classification of land cover. The thermal AC parameters obtained were applied to the calibrated at-sensor radiance band 6 (high gain) data to compute the surface-leaving radiance with the emissivity values obtained for each site. The Planck equation was inverted using the calibration constants to derive LST.
Keywords: Thermal Remote Sensing; Earth Observation Satellites (EOS); Mapping; Gas Flaring; Land Surface Temperature (LST); Emissivity